Genome-wide association study reveals BET1L associated with survival time in the 137,693 Japanese individuals - Masato Akiyama; Saori Sakaue; Atsushi Takahashi; Kazuyoshi Ishigaki; Makoto Hirata; Koichi Matsuda; Yukihide Momozawa; Yukinori Okada; Toshiharu Ninomiya; The Biobank Japan project; Chikashi Terao; Yoshinori Murakami; et al. (Communications Biology, 2023)
A genome-wide association study in the BioBank Japan cohort reveals new locus, BET1L, which is associated with survival time in a Japanese population.